2023
DOI: 10.2174/1567201819666220509162659
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing Properties of Pelargonium Graveolens L'Hér Extract Lipogel: In-Vivo Evaluation in an Animal Burn Model

Abstract: Background: Pelargonium graveolens L'Hér has traditionally been used to reduce skin inflammation, and recent studies have confirmed antioxidant compounds in the plant's extract. The present study aimed to prepare a lipogel formulation from P. graveolens hydroalcoholic extract and evaluate its efficacy on the wound healing process in an animal model. Material and Methods: The aerial part extract of P. graveolens was prepared through percolation. Additionally, plastibase was prepared by mixing 5% of low-molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…: The potential treatment of wounds and ulcers using Pelargonium essential oil was observed, and it is also used traditionally for this purpose. 63 In a conducted study, a cream formulation containing P. graveolens essential oil was applied to a wound model. The results of the experiment showed that there was no significant difference in the antibacterial properties between the positive control group and the group treated with the essential oil.…”
Section: Anethum Graveolens Lmentioning
confidence: 99%
“…: The potential treatment of wounds and ulcers using Pelargonium essential oil was observed, and it is also used traditionally for this purpose. 63 In a conducted study, a cream formulation containing P. graveolens essential oil was applied to a wound model. The results of the experiment showed that there was no significant difference in the antibacterial properties between the positive control group and the group treated with the essential oil.…”
Section: Anethum Graveolens Lmentioning
confidence: 99%